Dizajniranje mixa tehnologijskog marketinga kao matematički problem odlučivanja - Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
Designing technological marketing mix (TM-MIX) in differenttraffic, transport and telecommunication systems has abasic feature of a ’decision-making problem’ (DMP ). The paperdiscusses mathematical constructs and procedures applicablein developing TM alternatives and in the choice of the bestcombination (composition) ofTM-mix. Algorithm for solving a’General Choice Problem’ is presented. Expert Choice Softwareand other decision-support tools have substantial theoreticalsupport in the denoted concepts, procedures and algorithms.